Patricios en contienda : cuadros de costumbres, reformas liberales y representación del pueblo en Hispanoamérica (1830-1880) - Martínez-Pinzón, Felipe, 1980- (North Carolina studies in the Romance languages and literatures ;, 2021)
"Patricios en contienda explores the ways in which cuadros de costumbres were deployed to nationalize local populations in Colombia, Ecuador and Venezuela as part of larger debates about how these national cultures should look like after Gran Colombia (1819-1830) disassembled. By placing cuadros de costumbres in its tumultuous context, this book shows how old elites proud of their Spanish ancestry - Colombian Jose María Vergara y Vergara (1831-1872) or Venezuelan Fermín Toro (1806-1865) - fought newer ones emerging from the War of Independence - Venezuelan general Jose Antonio Páez (1790-1873), his son Ramón Páez (1810-1894) or Italian geographer Agustín Codazzi (1793-1859) among others - in order to gain legitimacy in the transition from monarchical rule to republicanism. These new and old patricians chose different social types to write about and compiled them into albums, memoirs or 'literary museums' in order to create pueblos that reflected their own personal histories and political projects. They did so by adding and subtracting diverse historical experiences homogenized as picturesque types, such as the tobacco roller or the llanero. In response to the mechanisms of inclusion and exclusion, marginalized members of the elites-such as Colombian Josefa Acevedo de Gómez (1803-1861) or Ecuadorian Dolores Veintimilla (1829-1857) - participated in these public debates about 'costumbres nacionales' by writing about left-out types or repurposing the sketch in order to write lives of indigenous peoples. Ultimately, by situating cuadros de costumbres within the periodicals where they first appeared, Patricios en contienda argues they ought to be read as a political tool - and placed along micro-biographies of illustrious men or serialized novels appearing in the press- through which their authors sought to define the new Republics in the midst of a shifting political landscape were heterogeneous populations were being refashioned as one single national 'pueblo'"--